Mighty scared : the amazing ways animals defend themselves [book with audioplayer] - Silver, Erin, 1980- ([Library Ideas, LLC], 2025)
"Learn about the wild, wacky and downright disgusting ways some animals react out of fear. Are you afraid of the dark? Of getting lost? Or of something you saw in a movie? Maybe someone laughed at you for being scared or called you a chicken. That's okay! In fact, it's how humans stay safe in scary situations. While people might run or scream, animals have amazing ways of protecting themselves when they're afraid. Fulmar birds vomit, Texas horned lizards shoot blood from their eyes and hagfish slime their enemies. Full of incredible and sometimes gross animal facts, Mighty Scared explores how mammals, insects, fish and birds around the world respond when scary predators are near." --